A simple representation of spallation neutron energy spectra for 'back of the envelope' estimates. (March 2017) - Findlay, D.J.S.
Abstract: A simple approximate easy-to-use analytic formula is suggested for the absolute integrated-over-angle energy spectrum of neutrons from a high- Z spallation neutron target driven by 500–1500 MeV proton beams. Overall, the formula is probably reliable to within a factor 2–3, and could be useful for quickly making rough 'back of the envelope' estimates. Highlights: A simple formula for spallation neutron energy spectra for rough estimates. Probably reliable to within a factor 2–3. Useful for making back-of-the-envelope estimates of induced activities.